TANTANGAN DAN PENGARUH PEMBELAJARAN JARAK JAUH DI MASA PANDEMI MAHASISWA POLITEKNIK NEGERI MADIUN - Yopie Diondy Kurniawan; Halleina Rejeki Putri Hartono (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2022)
The current Covid-19 pandemic has an impact on high-level lecturers. Madiun State Polytechnic as one of the state higher education institutions in Indonesia is required to follow changes in the learning method, namely distance learning (PJJ), which was originally fully done face-to-face. The location of the campus in Madiun City with diverse student origins and far from urban areas is a challenge for the institution. This study aims to reveal the extent to which distance learning during the Covid 19 pandemic is effective and efficient, can this distance learning achieve the learning and academic goals of Madiun State Polytechnic students. From the results of research at the Madiun State Polytechnic, the learning environment and Community Interaction have a positive and significant impact on the academics of Madiun State Polytechnic students. The motivation variable has a positive effect but does not contribute significantly to the academics of Madiun State Polytechnic students. Where the motivational variable affects academics where student motivation is low, even students are less enthusiastic in carrying out learning in this pandemic situation.